Compensating Surplus and Equivalent Surplus in Long-Term Public Investment Effects Valuation - Foltyn-Zarychta, Monika (Nadwyżka kompensująca i nadwyżka ekwiwalentna w wycenie długoterminowych efektów inwestycji publicznych, 2010)
The effects of investments changing public goods that influence many generations, meet various obstacles in the appraisal process of such projects. The use of contingent and equivalent surpluses for public good changes valuation in the intergenerational perspective involves establishing the connection between purely economic assessment and some of ethical approaches that define the assignment of rights to the contemporary or future generations. When one of the ethical rules is assumed, it significantly influences the definition of the scope of intergenerational effect valuation.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 138, s. 28-42
Keywords: public investments; project appraisal